Influence of microwave energy on structural and piezoelectric response of Bi 4Ti 3O 12 ceramics - Aguiar, Ederson Carlos [UNESP]; Simões, Alexandre Zirpoli [UNESP]; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (American Scientific Publishers, 2010)
Bismuth titanate ceramics (Bi 4Ti 3O 12) with 10 wt% in excess of bismuth (BIT10) were prepared by the polymeric precursor method and sinterized in microwave (MW) and conventional furnaces (CF). The effect of microwave energy on structural and electrical behavior of BIT10 ceramics was investigated by means of X-ray diffraction (XRD), Scanning electron microscopy (SEM) and electrical measurements. The results of the BIT10 ceramics processed in the microwave furnace (MW) showed a high structural organization compared to conventional treatment (CF). Size of grains and dieletrical properties are influenced by annealing conditions while coercitive field is not dependent on it. The maximum dielectric permittivity (12000) was obtained for the sample sintered in the microwave furnace. Piezoelectric force microscopy images reveals that in-plane response may not change its sign upon polarization switching, while the out-of-plane response does with the influence of microwave energy. Copyright © 2010 American Scientific Publishers All rights reserved.
Keywords: Bi 4Ti 3O 12; Dielectric response; Microstructure; Microwave sintering; Piezoelectric force microscopy; Scanning electron microscopy; X-ray diffraction; Annealing condition; Bismuth titanate ceramics; Conventional furnace; Conventional treatments; Dielectric permittivities; Electrical behaviors; Electrical measurement; Microwave energies; Microwave furnace; Out-of-plane; Piezoelectric response; Polarization switching; Polymeric precursor methods; Structural organization; X ray diffraction